Between endothelial activation and stress index (EASIX) and mortality in acute respiratory distress syndrome (ARDS) patients: a multicenter retrospective study - Chen, Juan; Lv, Jing; Liu, Meijun; Dai, Xue; Deng, Wang (Frontiers in Physiology, 2025)
BackgroundThe Endothelial Activation and Stress Index (EASIX), calculated as [lactate dehydrogenase (U/L) × creatinine (mg/dL)] ÷ platelet count (109/L), serves as a reliable biomarker for endothelial dysfunction. Endothelial damage significantly contributes to the pathophysiological mechanisms underlying acute respiratory distress syndrome (ARDS). However, the relationship between EASIX and ARDS patients remains to be fully elucidated.MethodsTo evaluate the relationship between EASIX and outcomes in patients with acute respiratory distress syndrome (ARDS), in two cohorts we used Cox proportional hazards models and applied restricted cubic spline methods. Then we stratify EASIX into higher Log2_EASIX and lower Log2_EASIX groups, matched baseline data from the two stratified groups in both cohorts using propensity score matching to reduce confounding bias. Additionally, we further analyzed the differences in clinical outcomes between the higher Log2_EASIX and lower Log2_EASIX groups and performed Kaplan-Meier analysis on the matched data.ResultsIn the MIMIC-IV cohort, compared to the survival group, within the 28 days, the non-survival group had higher Log2_EASIX (Survival: Non-survival = 1.35 [0.16, 2.80]: 2.08 [0.79, 3.59], P = 0.002),and in the CQMU cohort, the non-survival group had higher Log2_EASIX (Survival: Non-survival = 1.91 [1.48, 2.43]: 2.34 [1.89, 3.01], P < 0.0001), Even after adjusting for potential confounders, individuals exhibiting elevated Log2_EASIX values still faced a greater risk of mortality during hospitalization and at 28-, 60-and 90-day post-admission.ConclusionElevated EASIX levels were found to be positively correlated with a higher risk of mortality in patients with ARDS. Assessing EASIX levels could be a promising biomarker for predicting overall survival in ARDS.